IS TAILORED ANTICOAGULATION MANAGEMENT FEASIBLE IN PATIENTS WITH ARTERIAL HYPERTENSION AFTER THEIR FIRST CLINICAL ECG-DOCUMENTED PAROXYSMAL ATRIAL FIBRILLATION EPISODE?. (April 2021) - Papakonstantinou, Panteleimon; Simantirakis, Emmanuel; Kanoupakis, Emmanuel; Parthenakis, Frangiskos; Vardas, Panos
Abstract : Objective: Long-term anticoagulation therapy is usually recommended for most of the patients with hypertension as the CHA2DS2-VASc score is at least 1. However, this is to some extent arbitrary, because it is not known if these patients will continue to present AF episodes. Furthermore, recent data showed that only AF episodes with a duration >24 hours increased significantly the risk of ischemic stroke. We tested the hypothesis whether the identification of the exact natural course of AF would have a favorable impact on AF-personalized anticoagulation, by facilitating the selection of patients in need of antithrombotic treatment on the basis of their AF recurrence profile. Design and method: Consecutive patients who received an implantable loop recorder-ILR (Reveal XT 9529; Medtronic, Minneapolis, Minnesota, USA) after their first ECG-documented symptomatic episode of paroxysmal AF were enrolled. Low recurrence rate and short durations episodes of the arrhythmia was defined as <5 AF episodes/year and </=24 h AF episodes respectively. Results: Thirty (30) consecutive patients (mean age 66.9 +/− 10 years; 14 men); 25/30 (83.3%) with arterial hypertension, were included in the study. The follow-up period lasted for 34, 63 +/− 2, 96 months after the implantation of the ILR. The mean CHA2DS2-VASc score was 2.83 ± 1.66. Three patients (10%) had no AF recurrence, while 4 patients (13.3%) presented only one episode during the three-year follow-up period. Almost half of the patients (46.7%) had a low recurrence rate (<5 episodes/year), while the majority of patients (19/30) suffered from episodes with maximum duration of </=24 h. Eleven patients (36.7%) presented either no episode or a low recurrence rate with episodes lasting </=24 h. Conclusions: A significant percentage of patients either suffer 0–1 AF recurrence (23.3%) after their first episode or show a low recurrence rate (46.7%). Most patients present episodes of short duration (<24 h). If these findings are confirmed by larger studies, they could have an impact in the strategy towards a more personalized approach, in the long-term AF anticoagulation management, especially in the era of non-Vitamin K antagonists and devices that provide long-term cardiac rhythm monitoring.